2014
DOI: 10.1128/jb.01465-13
|View full text |Cite
|
Sign up to set email alerts
|

YlxM Is a Newly Identified Accessory Protein That Influences the Function of Signal Recognition Particle Pathway Components in Streptococcus mutans

Abstract: Streptococcus mutans is a cariogenic oral pathogen whose virulence is determined largely by its membrane composition. The signal recognition particle (SRP) protein-targeting pathway plays a pivotal role in membrane biogenesis. S. mutans SRP pathway mutants demonstrate growth defects, cannot contend with environmental stress, and exhibit multiple changes in membrane composition. This study sought to define a role for ylxM, which in S. mutans and numerous other bacteria resides directly upstream of the ffh gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…YidC2 works in concert with the signal recognition particle (SRP) pathway. The SRP is comprised of Ffh, a small cytoplasmic RNA, and the YlxM accessory protein present only in Gram-positive bacteria [63]. The SRP targets the ribosome nascent chain complex to the membrane via a reversible interaction of Ffh with the SRP receptor FtsY.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…YidC2 works in concert with the signal recognition particle (SRP) pathway. The SRP is comprised of Ffh, a small cytoplasmic RNA, and the YlxM accessory protein present only in Gram-positive bacteria [63]. The SRP targets the ribosome nascent chain complex to the membrane via a reversible interaction of Ffh with the SRP receptor FtsY.…”
Section: Resultsmentioning
confidence: 99%
“…Cell lysate samples were electrophoresed on 4-20% precast gels (Bio-Rad Laboratories, Hercules, CA) in Tris-Glycine-SDS buffer. Replicate gels were stained with Coomassie Blue R 250 or transblotted onto Immobilon polyvinylidene difluoride (PVDF) membranes (Bio-Rad Laboratories, Hercules, CA), reacted with affinity-purified YidC1 or YidC2 C-terminal-specific polyclonal rabbit antibodies (1:1000) [26], or anti-Ffh or anti-FtsY polyclonal rabbit antisera (1:1000) [63], followed by horseradish peroxidase-labeled anti-rabbit IgG (MP Biomedicals, Irvine, CA) (1:5000), and developed using the enhanced-chemiluminescence (ECL) Western blotting system (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Further, repressing HBsu increased scRNA production and led to precursor protein accumulation, showing an important function of HBsu in the SRP targeting pathway (Yamazaki et al ., ). Similarly, an SRP accessory protein was recently identified in S. mutans (Williams et al ., ). The gene encoding YlxM is located directly upstream of ffh in S. mutans , a conserved gene organization in most gram‐positive and some gram‐negative bacteria.…”
Section: Oral Streptococci: Breaking the Moldmentioning
confidence: 97%
“…A helix‐turn‐helix protein, YlxM, was predicted to be a DNA‐binding protein and suspected to regulate SRP component transcription/translation (Samuelsson et al ., ; Oganesyan et al ., ). Surprisingly, functional studies showed no evidence of gene regulatory function, but rather a direct interaction between YlxM and both Ffh and the scRNA (Williams et al ., ). In addition, YlxM increased GTP hydrolysis of Ffh.…”
Section: Oral Streptococci: Breaking the Moldmentioning
confidence: 97%
“…Integral membrane proteins are translocated cotranslationally. As soon as their nascent chain exits the ribosome, they are recognized by the signal recognition particle (SRP) 1 , a ribonucleoprotein complex composed of the GTPase Ffh, its newly identified modulator YlxM (32) and the SRP 4.5S RNA. The SRP guides the ribosome-nascent chain complexes to the SecA-SecYEG translocon via the transmembrane SRP receptor FtsY (33,34).…”
mentioning
confidence: 99%